Is type 2 diabetes related to leukoaraiosis? an updated review. (16th March 2015) - Del Bene, A.; Ciolli, L.; Borgheresi, L.; Poggesi, A.; Inzitari, D.; Pantoni, L.
<x xml:space="preserve">Abstract</x> A significantly increased interest has been dedicated to the study of the effects of diabetes mellitus (DM) on the brain. DM is associated with an increased risk of stroke and cognitive decline. In patients with DM, neuroimaging discloses with high‐frequency structural changes, such as cerebral atrophy, infarcts and white matter lesions, also called leukoaraiosis (LA), an expression of small vessel disease. A previous review showed a relation between DM and both cerebral atrophy and lacunar infarcts, while the question about the relation between DM and LA remained unanswered. In this review, we provide an update on data on this last association. In the reviewed studies, we examined the presence of DM, other disease characteristics, such as duration and complications, and laboratory markers of the disease such as blood glycated hemoglobin (HbA1c), insulin resistance, insulin concentrations and their association with LA. About 40% of the reviewed studies reported a statistically significant association between DM and LA. Long‐standing DM and a poor glycemic control were associated with severe LA. Studies using innovative MRI techniques, such as diffusion tensor imaging (DTI), reported a significant association between microstructural white matter alterations and DM. This review highlights more firmly than previously reported the existence of a relation between DM and both presence and severity of LA. These results are possibly due to more sensitive and advanced imaging techniques recently used to study the extent of LA. However, because of the heterogeneous methodology used in the reviewed studies, a definitive conclusion cannot be drawn.